2018
DOI: 10.1108/ebr-12-2016-0156
|View full text |Cite
|
Sign up to set email alerts
|

The impact of CEO arrogance on top management team attitudes

Abstract: Purpose -The purpose of this paper is to test the effects of CEO arrogance on key attitudes of a company's top management team (TMT). Design/Method/Approach -An experimental design involving a business simulationis employed to test the effects of a CEO's perceived arrogance and humility on the TMT in a boardroom setting. Findings -The study finds that, as predicted, arrogant CEOs adversely impacts TMT engagement, cohesiveness, collaboration and consensual decision-making. Thus, the higher the level of CEO arro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
29
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 67 publications
4
29
0
1
Order By: Relevance
“…A good leadership style shown by leaders is the driving force for the direction of the any organisations. Toscano et al (2018) believed that the levels of positive attitudes shown by followers and subordinates; team members, are highly dependent and determined by levels of humility exuded by the leader. Liborius (2017) further supported by stating that influencing characters such as integrity, humility and forgiveness are very crucial in determining good leadership.…”
Section: Impact Of Arrogance Leadership On Individuals In Organisationmentioning
confidence: 99%
See 4 more Smart Citations
“…A good leadership style shown by leaders is the driving force for the direction of the any organisations. Toscano et al (2018) believed that the levels of positive attitudes shown by followers and subordinates; team members, are highly dependent and determined by levels of humility exuded by the leader. Liborius (2017) further supported by stating that influencing characters such as integrity, humility and forgiveness are very crucial in determining good leadership.…”
Section: Impact Of Arrogance Leadership On Individuals In Organisationmentioning
confidence: 99%
“…Arrogant leaders are leaders acting without the consent of team members causing resistance and rebellion amongst their members (Haan, Britt, & Weinstein, 2007;Toscano, Price, & Scheepers, 2018). In short, a person who has a high sense of superiority is also inaccessible and usually unapproachable; he is viewed as arrogant (Toscano et al, 2018;Trumpeter, Watson, & O'Leary, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations